Increasing the "Productivity" of the Academic Sector and Ensuring Cooperation with the Large Corporate Sector in Japan - K. S. Kostyukova (Модернизация, инновация, развитие)
Purpose: the main purpose of this article is to review the Japanese policy to promote cooperation between the academic and large corporate sectors in the field of science and technology, and to analyze its role in the formation of the innovation system in Japan.Methods: this article is based on the analysis of scientific and analytical materials on the problem of research. The factual basis is the framework documents of the Cabinet of Japan.Results: the article provides a brief retrospective review on the support policy for universities and large corporate sector cooperation, identifies the key factors for the establishment of intersectoral cooperation; identifies the problem areas of the implemented policy that hinder the achievement of the set goals. The relative failure of the applied measures in the sphere of venture business support, commercialization of technologies and other instruments was noted. The hypothesis is put forward about the insufficiency of government efforts to monitor and analyze the activities already implemented, the lack of practice of taking into account failures in the formation of new programs and projects. Also revealed contradictions between the support programs implemented through various government agencies, which also leads to the inefficiency of scientific and technological projects and the establishment of dialogue with the corporate sector, including the need to resolve bureaucratic disagreements. It is also necessary to emphasize, that Japanese experience in implementing of science and technology and innovation policy is very important for Russian economic development. In particular, special attention is paid to study foreign experience in creating an effective mechanism of academic and private sectors interaction, where the key-supporting role is played by government in case of Japan. No doubt, it is not justified to try to copy any foreign institutional system, but the analysis of the negative and positive effects of foreign economic system cases is very valuable for self-institutional mechanisms development.Conclusions and Relevance: the analysis leads to the conclusion that Japan has not yet completed the transformation to a modern model of the national innovation system, the current problem is the weakness of relations between the academic and corporate sectors. At the same time, there is an excessive, "paternalistic" role of the state in the organization of intersectoral interactions, in the absence of attention to the optimization of conditions and incentives for this kind of dialogue. The Japanese government actively supports and tries to develop the practice of "open innovation" business model, but due to the obsolescence of existing institutional structures, as well as their unpreparedness to the development and perception of radically new business models, has not yet been able to achieve concrete sustainable results.